Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/7135043
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Reinforcement Learning-Based Path Control and Optimization for Unmanned Ships

Abstract: Unmanned ship navigates on the water in an autonomous or semiautonomous way, which can be widely used in maritime transportation, intelligence collection, maritime training and testing, reconnaissance, and evidence collection. In this paper, we use deep reinforcement learning to solve the optimization problem in the path planning and management of unmanned ships. Specifically, we take the waiting time (phase and duration) at the corner of the path as the optimization goal to minimize the total travel time of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…This also indicates that the vegetation index by combining multisource satellite images is still a good measure of the long-term vegetation cover status. Therefore, based on the typical regional statistical results and the spatial distribution of NDVI and RVI of the four types of satellite images in the test area, there is a strong correlation between the long-term serial vegetation cover and the vegetation indices extracted from the multisource satellite images in the test area [ 17 ].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This also indicates that the vegetation index by combining multisource satellite images is still a good measure of the long-term vegetation cover status. Therefore, based on the typical regional statistical results and the spatial distribution of NDVI and RVI of the four types of satellite images in the test area, there is a strong correlation between the long-term serial vegetation cover and the vegetation indices extracted from the multisource satellite images in the test area [ 17 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Several studies have shown that the vegetation indices extracted from satellite images can be a good measure of surface vegetation cover and its spatial and temporal evolution characteristics. For example, the extraction of vegetation indices using Landsat TM/OLI images [ 1 – 5 ], SPOT satellite images [ 6 – 8 ], HDS-1/2 satellite images [ 9 – 11 ], and Sentinel-2 satellite images [ 12 14 ] has provided basic data support for the spatial and temporal evolution of vegetation cover in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The DRBM model can be considered as a two-layer model, where both the visible layer and the label layer are the input sample data, and the hidden layer can be used to sample the joint probability distribution and conditional probability distribution of the visible and label layer data. Since an animation belongs to only one style, the label layer can be coded as “single heat”; that is, the label layer is set as a binary neuron, and only the neuron corresponding to the label has a value of 1 and is active [ 21 , 22 ].…”
Section: Animation Design Model Based On Two-layer Rbmmentioning
confidence: 99%
“…Since ocular pathologies often have no obvious symptoms in their early stages and are easily overlooked by patients, resulting in irreversible visual impairment of varying degrees by the time patients come to the clinic with ocular symptoms, routine screening, and early diagnosis of ocular diseases are critical [ 1 , 2 ]. Meanwhile, the rich biological information of fundus images can reflect other tissues, organs, or systems and is expected to be applied.…”
Section: Introductionmentioning
confidence: 99%